INTEGRATING TMA WITHIN “CLAIM AND SUPPORT” STRATEGY ON STUDENTS’ CRITICAL THINKING ON ARGUMENTATIVE ESSAY - Eko Suhartoyo; Dzurriyyatun Ni'mah (JEELL (Journal of English Education, Linguistics and Literature) English Department of STKIP PGRI Jombang, 2020)
Based on the previous research, it was found that the Think Write Pair Share technique was ineffective in improving students’ critical thinking skill, and due to the fact that during the process of learning to write argumentative essay, student commonly encounters various obstacles at determining the opinion of a topic which should be supported by logical reasons and appropriate evidences in the form of facts, then this research aimed at investigating the effectiveness of Toulmin’s model of argumentation within “Claim and Support” strategy on undergraduate students’ critical thinking ability on argumentative essay. Thus, this current research employed a quasi-experimental design with a pretest-posttest and nonrandomized control group design. Students’ critical thinking ability was measured by a writing test in the form of argumentative essay test. The data analysis in this research employed analysis of covariance (ANCOVA). This research revealed that Toulmin's model of argumentation within “Claim and Support” strategy was ineffective to improve students' critical thinking in their argumentative essay.